Youth outside the mainstream. Beekeeping as a profession and lifestyle = Młodzi poza mainstreamem. Pszczelarstwo jako zawód i styl życia - Pokrzyńska, Magdalena (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This text presents different faces of modern beekeeping, with particular reference to the characteristics of Polish beekeeping and personality traits of young apiarists. An important factor shaping this face is the history of beekeeping, and that is why the author recalls traditional features and facts from the history of this activity, while simultaneously referring to the globally noticeable trends.
Keywords: lifestyle; youth; dying professions; beekeeping; styl życia; młodzież; znikający zawód; pszczelarstwo